Use of eye-tracking to evaluate human factors in accessing neonatal resuscitation equipment and medications for advanced resuscitation: A simulation study - Chen, Linda Gai Rui; Law, Brenda Hiu Yan (Frontiers in Pediatrics, 2023)
Introduction: Emergency neonatal resuscitation equipment is often organized into “code carts”. Simulation studies previously examined human factors of neonatal code carts and equipment; however, visual attention analysis with eye-tracking might further inform equipment design. Objectives: To evaluate human factors of neonatal resuscitation equipment by: 1) comparing epinephrine preparation speed from adult pre-filled syringe vs medication vial, 2) comparing equipment retrieval times from two carts and 3) utilizing eye-tracking to study visual attention and user experience. Methods: We conducted a 2-site randomized cross-over simulation study. Site 1 is a perinatal NICU with carts focused on airway management. Site 2 is a surgical NICU with carts improved with compartments and task-based kits. Participants were fitted with eye-tracking glasses then randomized to prepare two epinephrine doses using two methods, starting with an adult epinephrine prefilled syringe or a multiple access vial. Participants then obtained items for 7 tasks from their local cart. Post-simulation, participants completed surveys and semi-structured interviews while viewing eye-tracked video of their performance. Epinephrine preparation times were compared between the two methods. Equipment retrieval times and survey responses were compared between sites. Eye-tracking was analyzed for areas of interest (AOIs) and gaze shifts between AOIs. Interviews were subject to thematic analysis. Results: Forty HCPs participated (20/site). It was faster to draw the first epinephrine dose using the medication vial (29.9s vs 47.6s, p<0.001). Time to draw the second dose was similar (21.2s vs 19s, p=0.563). It was faster to obtain equipment from the Perinatal cart (164.4s v 228.9s, p<0.027). Participants at both sites found their carts easy to use. Participants looked at many AOIs (54 for Perinatal vs 76 for Surgical carts, p<0.001) with 1 gaze shifts/second for both. Themes for epinephrine preparation include: Facilitators and Threats to Performance, and Discrepancies due to Stimulation Conditions. Themes for code carts include: Facilitators and Threats to Performance, Orienting with Prescan, and Suggestions for Improvement. Suggested cart improvements include: adding prompts, task-based grouping, and positioning small equipment more visibly. Task-based kits were welcomed, but more orientation is needed. Conclusions: Eye-tracked simulations provided human factors assessment of emergency neonatal code carts and epinephrine preparation.